Person matters in impersonality. (4th May 2022) - Berro, Ane; Odria, Ane; Fernández, Beatriz
Abstract: The Basque impersonal is a detransitivized construction where the internal argument is the only overt argument and the external argument, although semantically present, does not have any morphological reflex. This article argues that, despite its intransitive shape, the impersonal involves a particular kind of Voice projection that we term defective . For case and agreement, being defective means having no uninterpretable ϕ features and no Case to assign. However, a silent person pronoun is introduced in its specifier position, and thus, there are two arguments within VoiceP. The two arguments compete to value the ϕ features of the next functional head, namely T. With this analysis we account for the main properties of the impersonal, such as the syntactic activeness of the implicit external argument and the person constraint on the internal argument.